152k views
2 votes
If B = w + 1 and A = 2w + 1 find an expression that equals 2B + 3A in standard form

User Ari Gold
by
7.3k points

1 Answer

1 vote

Answer:8w + 5

Explanation:

To find an expression that equals 2B + 3A in standard form, we first substitute the expressions for B and A using the given values:

2B + 3A = 2(w + 1) + 3(2w + 1)

Simplifying the expression by multiplying out the brackets and collecting like terms, we get:

2B + 3A = 2w + 2 + 6w + 3

= 8w + 5

Therefore, the expression that equals 2B + 3A in standard form is 8w + 5.

User Utahwithak
by
6.7k points